Adresat dziecięcy w tłumaczeniach Winnie-the-Pooh A.A. Milne'a na język polski i słowacki - Sojda, Sylwia (Przekłady Literatur Słowiańskich, 2012)
Children’s recipient in translations of Winnie-the-Pooh by A.A. Milne into Polish and Slovak The paper presents a comparison of Polish and Slovak translations of A.A. Milne’s book Winnie-the-Pooh, made by Irena Tuwim, Monika Adamczyk-Garbowska, Margita Príbusová and Stanislav Dančiak. The main object is to show determinants of honorification in the children’s style in compared languages: behavitives, adressative forms, deminutives and hypocoristics. The author also focuses on problems connected with the translation of plays on words, short rhyme poems and children’s songs. Key words: children’s recipient, honorification, deminutives, hypocoristics, behavitives